Features of the Development in the Market of the Passenger Transport Services in the Russian Arctic - Natalia A. SEROVA (Communications of International Proceedings, 2021)
This research aims at establishing major tendencies and features of the development in the market of the passenger transport services and their accessibility for the population of the Arctic zone in the Russian Federation. The authors have calculated the main indicators that describe the level of availability of the railway and automotive public transport services in the arctic regions in 2000-2019, and namely, an intensity factor for the spatial movement of the population by public transport and a level of the transport system focus on the satisfaction of the population’s needs. It is established that, in a twenty-year period, the population’s travel mobility in the Arctic regions irreversibly reduced while the transport system was re-oriented to the interests of companies that may imply both the decrease in the transport services accessibility for the citizens of the Russian Arctic and, in general, the reduction in the degree of the comfortable habitation of people in this territory.
Keywords: Russian Arctic; transport mobility; road transport; rail transport